(8х+1)(2х-3)-1=(4х-2)² х⁴-26х²+25=0 4х³-х²=0 (х²-5)²-3(х²-5)-4=0

Andriuy2003 Andriuy2003    1   02.03.2019 23:40    2

Ответы
blurryriden blurryriden  23.05.2020 22:50

1) 16х² - 24х + 2х - 3 - 1= 16х²- 16х +4

- 6х = -8

х=4/3

2) х²=а     биквадратное уравнение

а²-26а +25 =0

Д=576=24²

а= (26-24)/2=1

а= (26+24)/2= 25

х²=1  и  х²=25 

х=1  х=-1   х=5   х=-5

 

3)х²·(4х-1)=0

х=0  и 4х-1=0  4х=1   х=1/4 

4)пусть (х²-5) это будет а, тогда а²-3а-4=0  Д=25   а=4 и  а = -1

х²-5=4   и х²-5=-1 

х²=9 и х²=4, тогда х=3 х=-3 х=2 и х=-2 

 

 

 

 

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра